SAT0435 A1G T-Type Calcium Channel is Expressed in Human Fetal Hearts and Has an Extracellular Epitope Bound by Autoantibodies from Congenital Heart Block Maternal Sera. (23rd January 2014) - Strandberg, L. S.; Cui, X.; Rath, A.; Liu, X.; Silverman, E. D.; Siragam, V.; Ackerley, C.; Su, B. B.; Yan, J. Y.; Capecchi, M.; Biavati, L.; Accorroni, A.; et al.
Abstract : Background: Background: Congenital heart block (CHB) is a transplacentally acquired autoimmune disease associated with anti-Ro/La maternal autoantibodies and is characterized primarily by atrioventricular (AV) block of the fetal heart. Since the Ro/La autoantigens are intracellular proteins, they are not likely the targets of these maternal autoantibodies and likely cross-react with other proteins on the surface of cardiomyocytes. Objectives: Objectives: This study aims to investigate whether the α1G T-type calcium channel is expressed in human fetal hearts, and if maternal serum antibodies from CHB affected pregnancies bind to the α1G T-type calcium channel subunit in human fetal hearts. Methods: Methods: Expression of α1G was demonstratedin human fetal hearts by RT-PCR, and by Western Blot analysis of human fetal heart lysates. Immunological methods such as Western blot, ELISA, immunofluorescence and flow cytometry were utilized to demonstrate the binding of antibodies in serum from CHB affected pregnancies to the α1G protein on the surface of human fetal cardiomyocytes. Results: Results: We demonstrate differential mRNA expression of CACNA1G (α1G gene) and CACNA1H (α1H gene) in the AV junction of human fetal hearts compared to the apex (18-22.6 weeks gestation). Immunoprecipitation and Western blot analysis of α1G from human fetal hearts (20-22 wks gestation) demonstrates reactivity of maternal serum from CHB affected pregnancies but not from controls. Immunofluorescence (IF) staining and flow cytometry analysis also demonstrates expression of T-type Ca 2+ channel subunits in cardiomyocytes from 20-22 week old human fetal hearts. ELISA was used to assay the reactivity of sera from mothers with pregnancies affected by CHB and from controls to a series of peptides derived from the amino acid sequences of extracellular regions of α1G . Antibody reactivity to a peptide designated as p305 [corresponding to aa305-319 of the extracellular loop linking transmembrane segments S5-S6 in α1G repeat I], was significantly higher in the CHB maternal sera compared to controls (p<0.05). Reactivity was also demonstrated to the corresponding region of α1H by all CHB sera that were reactive to the α1G peptide (7/15 amino acids conserved). Conclusions: Conclusions: These results taken together indicate that α1G and possibly α1H are bound in extracellular regions by autoantibodies found in CHB maternal serum. Autoantibodies involved in CHB may thus cross-react and bind several fetal targets. Disclosure of Interest: None Declared